Katie the catsitter. Best friends for never - Venable, Colleen A. F. (Random House, 2022)
Katie tries to uncover who or what is behind events being blamed on Moustress, while she grapples with renewing her relationship with her best friend Beth who now has a boyfriend who's always hanging around.